Muawiyah Ibnu Abi Sufyan dan Pembentukan Dinasti Bani Umayyah, Kemajuan dan Kemunduran Dinasti Bani Umayyah - Sahbi Diti; Ansar Tohe (Al-Kindi, 2026)
This study aims to analyze the background of the establishment of the Umayyad Dynasty by Muawiyah ibn Abi Sufyan, examine the transformation of the Islamic political system, identify the administrative and civilizational achievements of the dynasty, and explain the factors that led to its decline. The research employed a qualitative method using a historical approach through library research. Data were collected from classical historical sources, academic books, and relevant scientific journals, and were analyzed using historical analysis, including heuristics, source criticism, interpretation, and historiography. The findings indicate that the establishment of the Umayyad Dynasty marked a significant transformation in the Islamic political system from a consultative (shura) model to a hereditary monarchy. Under Muawiyah's leadership, the dynasty succeeded in strengthening state administration, developing bureaucratic institutions, expanding its territory, and promoting economic, cultural, and architectural advancement. However, internal political conflicts, social inequality, tribal rivalries, discrimination against mawali, and the emergence of opposition movements, particularly the Abbasids, gradually weakened the dynasty and led to its collapse in 750 CE. The study concludes that the sustainability of a government depends not only on political and military power but also on effective governance, social justice, and inclusive leadership.